Analysis of ELENA's Usage: Harmonization of TAM and TPB - Widhiastuti, Ratieh; Farika, Ummi (Journal of Educational Science and Technology (EST), 2024)
This research analyzes perceptions of using ELENA from a student's perspective by harmonizing variables in the TAM and TPB theories. This research focused on students from the Department of Economic Education, Universitas Negeri Semarang (UNNES) class of 2021. Using the Slovin formula, a research sample of 205 students was obtained from 420 students. Research data was obtained using a questionnaire first tested for validity and reality. Descriptive analysis was used to determine the extent of students' perceptions of the research variables, and path analysis using the PLS method was used to test the research hypothesis. The research results show that perceived usefulness, attitude, subjective norms, and perceived behavioral control influence behavioral intention. Meanwhile, the variable that has no effect is perceived ease of use. According to the theoretical framework, attitude can mediate the influence of perceived usefulness and perceived ease of use on behavioral intention. Suggestions from this research to system developers are the need for a more straightforward manual guide and the need to simplify the system so that the system is user-friendly. Meanwhile, further research can use the same model as this research in other system applications.